Solifenacin in overactive bladder syndrome: pharmacoeconomic analysis - Iannazzo, Sergio; Pradelli, Lorenzo (Farmeconomia. Health economics and therapeutic pathways, 2008)
The overactive bladder (OAB) syndrome can be treated with behavioural, surgical and/or pharmaceutical interventions, mainly represented by antimuscarinic drugs. Solifenacin is a new antimuscarinic with selectivity for the bladder and it demonstrated good effectiveness, safety and tolerability. Scope of the present study is to investigate the pharmacoeconomic performance of the treatment with solifenacin, when compared to tolterodine and placebo, in Italian patients with OAB. The economic evaluation is performed with a simulation model, based on a Markov chain. The time horizon of the simulation is 52 weeks, with a 1-week cycle. The model simulates the outcomes and costs of the treatment with solifenacin (5 mg/die), tolterodine ER (4 mg/die) and no treatment in a cohort representative of the Italian population with OAB (estimated in about 1,400 thousands patients). The cost analysis is conducted mainly in the perspective of the patient, since drugs for the treatment of OAB are currently not included in the Italian reimbursement list. The results show that both treatments produce significative improvements in symptoms and quality of life, with an increase in costs of about 540-640 Euro/year with solifenacin and of 680-780 Euro/year with tolterodine. In the cost-utility analysis, solifenacin dominates tolterodine since it results more effective and less costly, and its cost cost-utility ratio with respect to no treatment is in the range 7,600-18,600 Euro/QALY. In the subgroup of patients incontinent at baseline and who best respond to the therapy (responders), the increase in costs with solifenacin results of about 100-400 Euro/year and the cost-utility ratio is 600-4,200 Euro/QALY. A supplementary scenario has been elaborated to explore the consequences of a hypothetical reimbursement decision by the Italian NHS. In this scenario, the NHS cost perspective is considered and the antimuscarinic drugs are assumed to be reimbursed at a half of the current retail price only to incontinent and responder OAB patients. The overall expenditure of such a decision, which yields clear health outcomes, is estimated in about 23 millions Euro, with a cost-utility ratio of about 600-2,400 Euro/year, suggesting an efficient allocation of sanitary resources.